La delimitación de la libertad contractual en virtud de exigencias sociales (2021)
This article presents the impact that social movements of the second half of the nineteenth century had on the doctrine of contracts in the twentieth century. An analysis of such influence is proposed in order to reformulate the problem of freedom of contract, in light of the Social Rule of Law, and the correlated reshaping of public order and good customs. In addition, a historical-originalist analysis is used to rethink the binding force of the contract.